Enhancing Organizational Resilience through Digital Innovation in Manufacturing - Fanani, Fajriannoor; Maratis, Jerry; Saiful Hadi, Muhammad; Magdalena, Lena; Ramirez, Santiago (APTISI Transactions on Management (ATM), 2024)
This study explores the role of digital innovation in strengthening organizational resilience within the manufacturing sector. By analyzing the integration of advanced technologies such as AI, IoT, and automation, the research investigates how these innovations improve operational flexibility, risk management, and adaptability to disruptions. A qualitative approach, including interviews with industry leaders, is employed to assess the impact. Findings demonstrate that digital innovation significantly enhances resilience, allowing manufacturers to respond efficiently to market volatility and operational challenges. The study concludes with recommendations for strategic implementation of digital tools.